Proceedings of the seminar on situation of the elderly in Bangladesh: what do we know? - lslam, Md Nazrul; Ahmed, Hasan Shareef (BRAC Research and Evaluation Division (RED), 2019)
There is a growing tendency of world's elderly (60 years and above) population and concentrating in the developing countries. By the year 2025, 72% of the world's elderly (858 million) population will be living in the developing countries. In 1980, China, India, Indonesia, Pakistan and Bangladesh were the five top ranking countries in terms of population lives in Asian and Pacific region. By the year 2025, these five countries will account for 44% of the world's elderly population. In Bangladesh, there are 6 million elderly population. This number will be 10 million by the year 2000 and 24 million by 2025. Bangladesh is one of the 20 countries with the largest elderly population. Traditionally, in Bangladesh, the responsibility for the welfare of the elderly lies with their children and the state has virtually no obligation to provide care for its elderly. Culturally a son, preferably the eldest one looks after their elderly parents. The daughters have no direct opportunity to look after her parents in old age due to two main reasons: there may be objections from her husband and her in-laws, and may view it as a shameful situation. What happens when there are no sons or when the sons are not available to look after the parents? Some elderly live on their own or have a poor relative stay with them to take care of them, while economic provision may be arranged by any children. Traditionally son provides food and shelter and his wife to takes personal care of her elderly parentsin- laws. Obviously, in case of a married elderly man, the primary caregiver is his wife if she is able. The riverse situation, husband caring for his wife, almost never occurs. However, majority of elderly people continue to live within extended family settings both in urban and rural areas, because social changes have not occurred significantly in the extended family. Moreover, the status of old people was not uniformly high in the past. It is also observed that there was a strong correlation between level of status of elderly and their economic power.